Revised soil erodibility K-factor for soils in the Czech Republic - Vopravil, J.,Vyzkumny Ustav Melioraci a Ochrany Pudy, Prague (Czech Republic); Janecek, M.,Vyzkumny Ustav Melioraci a Ochrany Pudy, Prague (Czech Republic); Tippl, M.,Vyzkumny Ustav Melioraci a Ochrany Pudy, Prague (Czech Republic) (Soil and Water Research - UZPI (Czech Republic), 2007)
This study was focused on soil susceptibility to water erosion expressed by the soil erodibility factor K. An original methodology for its determination suitable for Czech soil conditions was applied. In total ca. 5,000 soil pits from the whole territory of the country were processed and evaluated in detail. The main results of this study are K-factor values (means and variances) for the soil types, subtypes and varieties (represented in the database) according to the Taxonomic Classification System of Soils of the Czech Republic.